Effect of Omega-3 Eggs and Insoluble Dietary Fibre on the Physico Chemical, Proximate and Sensory Properties of Chicken Nuggets - Sathu, T; Joseph , Aaliya Tahseenand Rintu (Journal of Meat Science, 2023)
The study was aimed to select a suitable dietary insoluble fibre (DISF) for incorporating in functional chicken nuggets enriched with omega-3 eggs (OE). The wheat fibre (T1) and sorghum fibre (T2) at 4 per cent level were used separately as sources of  DISF in the formulation and were evaluated for various physico-chemical characteristics, proximate composition and sensory properties and compared with control C1 (without any functional ingredients) and C2 (enriched with 7.5 per cent OE). The DISF enriched chicken nuggets differed significantly (P
Keywords: Functional chicken nuggets; omega-3 eggs; wheat fibre; dietary insoluble fibre; sorghum fibre